2016
DOI: 10.1111/jfb.12949
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional rendering of otolith growth using phase contrast synchrotron tomography

Abstract: Abstract:We present a three-dimensional computer reconstruction of a plaice (Pleuronectes platessa) otolith from data acquired by the Diamond Light synchrotron, beamline I12, X-ray source, a high energy (53 -150 keV) source particularly well suited to the study of dense objects. Our data allowed non-destructive rendering of otolith structure, and for the first time allows examination of otolith annuli (internal ring structures) to be analysed in X-ray tomographic images. If 'Yes', provide details. Normally the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The determination of age in fishes by counting of annual rings on otoliths has been well established among researchers and fisheries managers for decades (Campana, ; Jones & Hynes, ). The method is still widely used (Koeda et al ., ; Robertson et al ., ; Uriarte et al ., ) though more recent approaches for otolith analysis, such as daily increment quantification, microchemistry, carbon dating, plasma mass spectrometry and three dimensional x‐ray scanning (Hippel et al ., ; Jones & Chen, ; Mapp et al ., ; Thorrold & Shuttleworth, ) are more powerful for age estimation. Reading of otolith annual rings, if validated, is still useful in ecological studies because it is cheap and more easily applied to large samples.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of age in fishes by counting of annual rings on otoliths has been well established among researchers and fisheries managers for decades (Campana, ; Jones & Hynes, ). The method is still widely used (Koeda et al ., ; Robertson et al ., ; Uriarte et al ., ) though more recent approaches for otolith analysis, such as daily increment quantification, microchemistry, carbon dating, plasma mass spectrometry and three dimensional x‐ray scanning (Hippel et al ., ; Jones & Chen, ; Mapp et al ., ; Thorrold & Shuttleworth, ) are more powerful for age estimation. Reading of otolith annual rings, if validated, is still useful in ecological studies because it is cheap and more easily applied to large samples.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al (2009) found an HU between 2,500 and 4,600 for asteriscus and lapillus of the carp otolith, respectively. Mapp et al (2016) and FAbOSA group (2002) did not present HU values. Nevertheless, other calcified structures are out of this range, e.g., scallop shells (744 HU) (Diez et al, 2013) and ureteral stone (1,350 HU) (Hameed et al, 2013).…”
Section: Exploring Otolith Density Variationmentioning
confidence: 85%
“…More recently, Yan et al (2009) used a high voltage (130 kV) and low current (30 µA), where higher photon energies penetrated the otolith and no information on density was captured. Mapp et al (2016) using monochromatic X-ray with 53 kV and no filter, rendered 3D imagery highlighting the growth rings. Although those authors considered that the objective proposed was reached, they reported some artifacts and did not experiment with other tomography settings.…”
Section: Protocol For the Optimal Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations